Co-creation and service innovation as performance indicators in the hospitality industry / Vivek Sharma and Dada Ab Rouf Bhat - Sharma, Vivek; Bhat, Dada Ab Rouf (Faculty of Hotel and Management, Universiti Teknologi MARA, Puncak Alam Campus, 2020)
This study aims at assessing the impact of co-creation on service innovation and also explores the dimensions of service innovation in the hotel industry as a performance indicator. The study was carried out through self-administered questionnaires to collect the data from 317 managers and frontline staff members of the luxury hotels using non-probability convenient sampling method. Structured equation modeling (SEM) was used to test the hypothesized relationship. The study outcomes revealed an imperative knowledge about co-creation and service innovation by determining its impact on hotel's overall performance in the hospitality industry. Further, there was a significant impact of co-creation on service innovation which in-turn positively contributes to financial and non-financial performance and lastly, the technological innovation and organizational innovations were found as the key dimensions of service innovation. Finally, this study establishes a foundation for future research and offers managerial guidance in this increasingly important area as it can be widened to different service sectors that may lead to a more generalized outlook of the whole service industry.